2022
DOI: 10.1007/s00192-022-05324-0
|View full text |Cite
|
Sign up to set email alerts
|

International urogynecology consultation chapter 3 committee 2; conservative treatment of patient with pelvic organ prolapse: Pelvic floor muscle training

Abstract: Introduction and hypothesis This manuscript from Chapter 3 of the International Urogynecology Consultation (IUC) on Pelvic Organ Prolapse (POP) describes the current evidence and suggests future directions for research on the effect of pelvic floor muscle training (PFMT) in prevention and treatment of POP. Methods An international group of four physical therapists, four urogynecologists and one midwife/basic science researcher performed a search of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 89 publications
0
23
0
1
Order By: Relevance
“…Pelvic floor muscle training has level 1/recommendation A to be effective in the treatment of UI and POP [55][56][57]. We have not found any RCTs or studies using other designs investigating the effect of PFMT on POP in women who engage in regular physical exercise or those who engage in heavy lifting or strenuous physical work.…”
Section: The Postpartum Periodmentioning
confidence: 99%
“…Pelvic floor muscle training has level 1/recommendation A to be effective in the treatment of UI and POP [55][56][57]. We have not found any RCTs or studies using other designs investigating the effect of PFMT on POP in women who engage in regular physical exercise or those who engage in heavy lifting or strenuous physical work.…”
Section: The Postpartum Periodmentioning
confidence: 99%
“…One study did specific PFMT as part of a Pilates class in addition to PFMT home training [ 23 ]. This study was presented and classified as PFMT by the authors and the results have been reported elsewhere [ 2 ]. Four studies (two reporting data on different outcome measures from the same study) compared PFMT with hypopressive exercise [ 10 , 24 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date there is 1A level/recommendation for PFMT as first-line treatment for POP [ 1 , 2 ]. No adverse effects have been reported from PFMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations